Metode Inovatif Dalam Pembelajaran Bahasa ArabSystematic Literature Review - Supriyanoor; Nirwanto, Rahmadi; Marsiah; Wahdah, Nurul (Institut Muslim Cendekia, 2025)
The utilization of technology and communicative approaches has evolved to enhance the effectiveness of learning. This study aims to identify forms of innovative methods in Arabic language learning that are relevant and effective over the past ten years in Indonesia. The research method employed is the Systematic Literature Review (SLR). A total of twenty-seven articles from Sinta-indexed journals (levels 2 to 5) published within the last ten years were collected, of which twenty-two articles were deemed relevant. The stages of this study include problem formulation, article collection, article screening, descriptive analysis, and conclusion drawing. Examples of innovative learning methods include 21st-century technology-based learning through the use of various digital applications such as Canva, Quizizz, Kahoot, Duolingo, and others. Based on the literature review conducted, it was found that innovations in Arabic language learning have developed significantly, particularly at the higher education level and through technology-based and creative media approaches. This is evidenced by the structural dimensions and categories identified in the articles, which indicate a significant trend toward 21st-century, integrative, and technology-based approaches in Arabic language instruction.